HUBUNGAN PENGETAHUAN PERAWAT TENTANG PENCEGAHAN - Darwati, Retno; Aminoto, Cokro; -, Ernawati (LPPM STIKES MUHAMMADIYAH GOMBONG, 2014)
Personal protective equipment(PPE)is very important for nurses whoarealways in contactwith the patient.Oneofthe equipments is a glove.Theuse of glovesisto protect the hands and contactwith blood,allkindsof body fluids,secretions, non-intact skin,mucous membranes and contaminated objects.Thenurse's knowledge is the basicfoundation of attitudesandbehaviors in PPEusage especially sterilegloves for infusion installationThe aim of this study is to determine the correlation between nurses’ knowledgeabout the prevention of infection with the complianceofusing sterile gloves when applying infusion on class iii ward of SarasHusadaHospital Purworejo.Thisis a descriptiveobservational correlationresearchusing crosssectionalapproach.Thepopulations in this studywere all nurses intheclass III inpatientward Saras HusadaGeneralHospital totaling 34 peopleand 31 of them weretaken as the samples. Questionnaires were used togain data about knowledge about preventionof infection. Observationsheetswere used to gain data about the sterile gloves usage.Dataanalysis used ChiSquare testOf 77.4%of the respondents had good category of knowledgeaboutinfectionprevention. 80.6% of therespondents complied to use sterile gloves when applying infusion. Thus mean that there is a correlation betweennurses’ knowledge about the prevention ofinfection with the complianceofusing sterile gloves when applying infusion on class Hospital. Keywords: Knowledge,InfectionPrevention,Compliance in steril using gloves